Food security, remoteness and consolidation of supermarket distribution centres: Factors contributing to food pricing inequalities across Queensland, Australia. Issue 1 (2nd January 2016) - Singh-Peterson, Lila; Lieske, Scott; Underhill, Steven J. R.; Keys, Noni
ABSTRACT: There is a clear association between food prices, affordability and issues of food security. Australian food supply chains have lengthened in recent years in response to consolidation policies of the dominant supermarkets, which have reduced the number of distribution centres in order to maximise economic efficiencies. This study presents a spatial analysis of a healthy food basket survey undertaken across Queensland, Australia in order to identify the primary determinants of food pricing. Ambiguity in the academic literature on this subject is largely due to limitations of the utilised methods. Our results indicate that food price variability is directly related to the type of store surveyed, and the distance of the surveyed store to the supermarket distribution centres in Brisbane, or urban centres on the east coast of Australia. Population size of towns and the level of social disadvantage observed in communities were indirect determinants of food prices. Therefore, in order to lessen the disadvantage already encountered by communities located in outer regional and remote areas who pay increasingly more for food than their urban counterparts, policy interventions need to move beyond subsiding food costs and consider the relationship between fuel prices and the lengthening of dominant food supply chains, in addition to the capacity of local supply chains.